COIL EMBOLISATION OF RUPTURED LEFT GASTRIC ARTERY ANEURYSM - Moreira, Mário (2020)
Visceral artery aneurysms are rare, with an estimated incidence of less than 2% in the general population. Left gastric artery aneurysm are particularly uncommon, accounting for 4% of all visceral aneurysms. Usually an incidental finding, they can manifest with rupture and be life threatening. The authors present a case of an 83 year-old male with haemorrhagic shock caused by a ruptured left gastric artery aneurysm. Coil embolization of afferent and efferent arteries was performed with good morphologic results. Management of a ruptured visceral aneurysm is aimed at controlling life-threatening bleeding usually by embolisation in the emergency setting.